2017
DOI: 10.1002/jso.24617
|View full text |Cite
|
Sign up to set email alerts
|

Modified frailty index predicts postoperative outcomes in older gastrointestinal cancer patients

Abstract: mFI was associated with the incidence of postoperative complications and mortality in older surgical patients with gastrointestinal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 52 publications
4
44
0
1
Order By: Relevance
“…Vermillion et al . reported 11‐mFI to be an independent predictor of major complications, prolonged LOS and mortality in surgical oncology patients. When the impact of an incremental increase in mFI score in open, emergent colectomies was analysed, Congiusta et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vermillion et al . reported 11‐mFI to be an independent predictor of major complications, prolonged LOS and mortality in surgical oncology patients. When the impact of an incremental increase in mFI score in open, emergent colectomies was analysed, Congiusta et al .…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [25] examined the impact of 5-mFI scores on 1928 patients who had combined liver and colon resections and reported mFI ≥ 2 to be significantly associated with increased odds of overall and serious morbidity. Vermillion et al [18] reported 11-mFI to be an independent predictor of major complications, prolonged LOS and mortality in surgical oncology patients. When the impact of an incremental increase in mFI score in open, emergent colectomies was analysed, Congiusta et al [23] found mortality, serious morbidity and reoperation to be significantly increased with each increase in mFI score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frailty screening is one example of an intervention that predicts post-op complications, length of stay, discharge to a skilled nursing facility, and mortality. 37,38 Assessing frailty can help patients and clinicians make informed decisions, including not to perform surgery on high-risk elderly patients and ensuring pre-and post-op supportive care for those who do undergo surgery. Specific research gaps for elderly surgical patients include communication, such as preoperative advance care planning and postoperative decision making, to ensure treatments are aligned with patient-oriented outcomes; identifying patient-centered outcomes that are of value to patients; evaluating high-quality palliative care in surgery; and testing methods to integrate palliative care into a rescue-oriented surgical culture.…”
Section: Surgerymentioning
confidence: 99%